1998
DOI: 10.1302/0301-620x.80b2.8351
|View full text |Cite
|
Sign up to set email alerts
|

Rupture of flexor pollicis longus tendon: A complication of volar plating of the distal radius

Abstract: We report three complete ruptures and one partial rupture of the flexor pollicis longus tendon in association with the insertion of a volar plate for the treatment of fracture of the distal radius. Rupture was associated with the chronic use of steroids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
84
1
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(92 citation statements)
references
References 0 publications
3
84
1
4
Order By: Relevance
“…The use of low-profile volar plate, correct screw length along with repair of the pronator quadratus to brachiradialis aponeurosis lowers the incidence of late frictional tear of the flexor as well as the extensor tendons. 11,14 The results of this retrospective study are comparable with those reported by various authors in terms of early functional recovery and acceptable radiological parameters. 3,6,11 The modified Green and O'Brien Score showed 5(21 Percent) excellent, 13(54 Percent) good, 5(21 Percent) fair, and 1(4 Percent) poor results at the latest follow-up.…”
Section: Modified Clinical-scoring System Of Green and O'briensupporting
confidence: 87%
“…The use of low-profile volar plate, correct screw length along with repair of the pronator quadratus to brachiradialis aponeurosis lowers the incidence of late frictional tear of the flexor as well as the extensor tendons. 11,14 The results of this retrospective study are comparable with those reported by various authors in terms of early functional recovery and acceptable radiological parameters. 3,6,11 The modified Green and O'Brien Score showed 5(21 Percent) excellent, 13(54 Percent) good, 5(21 Percent) fair, and 1(4 Percent) poor results at the latest follow-up.…”
Section: Modified Clinical-scoring System Of Green and O'briensupporting
confidence: 87%
“…However, some have observed that this muscle can be flimsy, especially in middle-aged women, and not provide significant plate coverage [2]. Early plate retrieval should be done if reduction or fixation is lost to prevent possible tendon irritation [1,7].…”
Section: Discussionmentioning
confidence: 99%
“…There are reports of the rupture of the flexor pollicis longus tendon due to mechanical attrition against the prominent distal edge of the plate [1][2][3][4][5]. In all of these reports the plate had been placed too distal.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to emphasize the watershed line as a landmark to prevent the plate being placed too proximal. In some cases, even if the plate is initially placed correctly, the collapse of the fracture makes the plate more prominent [1]. Scott and Duncan reported an isolated FPL rupture as a complication after osteosynthesis of the distal radius using a T-plate [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation